Assessment of awareness regarding human papilloma virus vaccine among medical students: a knowledge attitude and practice study - S., Shetty Theertha; Kamath, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Assessment of knowledge and awareness regarding human papilloma virus and cervical cancer among medical students. Methods: Questionnaire based prospective study of 200 III and IV year consenting medical students willing to be a part of the study. 25 questions were in the questionnaire and they were asked to tick in front of the answer which they felt was correct. 3 questions regarding demographic details were formulated. To assess knowledge, attitude and practice total of 10, 8 and 4 questions were formulated respectively. Score of 0, 1, 2 and 3 were given to answers for statistical analysis. Results: A 110 (55%) belonged to III year and 90 (45%) belonged to IV year. 112 (56%) were females and 88 (44%) were males. 180 (90%) were aware regarding agent causing cervical cancer. 77.8% of IV MBBS and all students of III MBBS knew the etiology. 98% knew the screening technique while 190 (95%) knew that vaccine availability for cervical cancer. 60% knew that the infection was sexually transmitted, and majority knew it is not curable with antibiotics. 70% knew route of administration while most were unaware about age of administration. 91% had not taken the vaccine while 41.5% would if offered. 73% knew the vaccine is ineffective against other STD’s and most agreed that vaccine should be in the national immunization schedule. 40% knew that men should be vaccinated while 79% would recommend it to others. Conclusions: Primary prevention of cervical cancer with vaccination is a novel concept. Health professionals can play a role in propagating this practice. Syllabus in medical schools must emphasize on such topics.